Penilaian Kualitas Air Sungai Weh Toweren Sebagai Salah Satu Inlet Danau Laut Tawar Di Kabupaten Aceh Tengah, Provinsi Aceh - Iriadi Ridwan; Hasri Iwan (Jurnal Lingkungan Almuslim, 2022)
River water quality in Indonesia is generally declining, including the water quality of the Weh Toweren River. The increasing population has an impact on increasing the waste discharge of residents into the waters. This increase also forced all sectors of production and consumption to increase, exacerbating the damage to rivers. The purpose of this study was to assess the water quality at the mouth of the Weh Toweren River. This research method uses a laboratory descriptive method. Determination of river water quality status using the Storage and Retrieval of Water Quality Data System (STORET) method. The parameters that are used as the basis for determining the status of river water quality are in the form of physical and chemical parameters. Physical parameters consist of temperature, brightness, turbidity, dissolved solids and suspended solids. Chemical parameters consist of pH, dissolved oxygen, biochemical oxygen requirements, chemical oxygen requirements, nitrates, nitrites, sulfates and fatty oils. The water quality data used is secondary data obtained from Dinas Lingkungan Hidup Kabupaten Aceh Tengah for the period 2017 to 2021. There are several parameters with a maximum value that has passed the Class I water quality standard including; TSS, BOD5 and COD. Based on The STORET analysis, the water quality status of the Weh Toweren River when compared to class I water quality standards is in Class B or "lightly polluted" with the STORET index (-8). Parameters that cause river water quality to be polluted include DO with a score of (-2), BOD5 (-2), COD (-4).